Extreme morphologies of mantis shrimp larvae - Haug,Carolin (2016)
ABSTRACT Larvae of stomatopods (mantis shrimps) are generally categorized into four larval types: antizoea, pseudozoea (both representing early larval stages), alima and erichthus (the latter two representing later larval stages). These categories, however, do not reflect the existing morphological diversity of stomatopod larvae, which is largely unstudied. We describe here four previously unknown larval types with extreme morphologies. All specimens were found in the collections of the Zoological Museum, University of Copenhagen and were collected during the Danish Dana Expedition round the world 1928-30. These new larval types all represent erichthus-type larvae, especially differing in their shield morphologies. The shield morphology ranges from almost spherical to rather disc-like, with sometimes extremely elongated spines, but only a general systematic assignment of the larvae was possible. Further investigations of these larvae are crucial to understand their life habits and ecological impact, especially as stomatopod and other crustacean larvae might have a much more important position in the marine ecosystems than their corresponding adults.